Inguinal bladder hernia: differentials for a male groin mass. Issue 11 (3rd November 2022) - Isaac, Daniel; Haris, Fondas; Panos, Dean; Diab, Jason; Clement, Zackariah
Abstract: Inguinal bladder hernia (IBH) is an uncommon occurrence in males with a groin mass. It may be present with lower urinary tract symptoms but is often asymptomatic, making it a diagnostic challenge. IBH is frequently an incidental finding during surgery, which increases the risk of iatrogenic injury of the bladder. This report examines the case of a 77-year-old male who experienced a painful, reducible right-sided groin mass with acute urinary retention. Investigations conducted through computed tomography exhibited a right indirect inguinal hernia containing omental fat and a portion of the urinary bladder. The patient underwent a right open herniorrhaphy with mesh repair. This report presents a systematic approach to differential diagnoses for a male groin mass and its relationship to IBH.